(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Alloy wheels are often composed of aluminum or magnesium metal or a combination of two metals. Usually, an alloy wheel made of magnesium or aluminum metal or sometimes a mixture of these two metals. Because the alloy wheel is lightweight, the vehicle speed is faster, but it is different from regular steel, but some alloy wheels are heavier than steel wheels of the same size. In automotive design, the industry searches for polymer composites as the best material for replacing aluminum alloys without significantly reducing the quality and reliability of the vehicle. Use of this material achieves quality optimization. In this project work, we are considering aluminum and composite fiber (carbon + sisal) rims. This article is about static analysis of aluminum and composite rims. By applying different loads and pressures, the entire wheel design of the two-wheeler is modeled and analyzed. The Al alloy wheel configuration of a two wheeler was selected for the investigation. Finite element analysis has been performed using ANSYS software to determine safe stress and displacement. For aluminum and composite materials, the goal is to determine stress, strain, and deformation using force as the boundary condition. A safety factor was later identified by using force as the boundary condition for these aluminum and composite materials. The pressure used as the boundary condition then reveals the stress, strain, and deformation of these composite materials and aluminum. Comparing these results, these results clearly show that mixed fiber material (carbon + sisal) is used as the best choice and can replace aluminum alloy with its good mechanical properties. Compared with aluminum alloy, hybrid composite material has a good safety factor value.